THE PECULIARITIES OF LOW-DOSE IONIZING RADIATION INFLUENCE ON MUSCLES METABOLISM IN EXPERIMENTAL ANIMALS - Stepanov, G.F.; Vastyanov, R.S. (World of Medicine and Biology, 2023)
The purpose of this study was to research the peculiarities of glycolytic processes manifestation in cardiac and striated muscles as a result of total irradiation exposure. 120 male rats were divided into 2 groups. Group 1 (n=20) – intact rats, group 2 (n=100) – rats that were exposed to ionizing gamma radiation. The animals were euthanized, blood was collected, the heart and the frontal group of thigh muscles were removed in which the pyruvate kinase and lactate dehydrogenase activities with its isozymes spectrum together with lactate and pyruvate content were measured. The pathophysiological mechanisms of radiation-induced energy supply reformation are aimed at strengthening of short-term processes of the energy supply to vital organs and systems for destroyed biochemical, physiological, functional and regulatory processes restitution and the sanogenetic mechanisms activation.